Methylation‐reprogrammed Wnt/β‐catenin signalling mediated prenatal hypoxia‐induced brain injury in foetal and offspring rats. Issue 8 (28th May 2018) - Zhang, Yingying; Zhang, Mengshu; Li, Lingjun; Wei, Bin; He, Axin; Lu, Likui; Li, Xiang; Zhang, Lubo; Xu, Zhice; Sun, Miao
Abstract: Prenatal hypoxia (PH) is a common pregnancy complication, harmful to brain development. This study investigated whether and how PH affected Wnt pathway in the brain. Pregnant rats were exposed to hypoxia (10.5% O2 ) or normoxia (21% O2 ; Control). Foetal brain weight and body weight were decreased in the PH group, the ratio of brain weight to body weight was increased significantly. Prenatal hypoxia increased mRNA expression of Wnt3a, Wnt7a, Wnt7b and Fzd4, but not Lrp6. Activated β‐catenin protein and Fosl1 expression were also significantly up‐regulated. Increased Hif1a expression was found in the PH group associated with the higher Wnt signalling. Among 5 members of the Sfrp family, Sfrp4 was down‐regulated. In the methylation‐regulating genes, higher mRNA expressions of Dnmt1 and Dnmt3b were found in the PH group. Sodium bisulphite and sequencing revealed hyper‐methylation in the promoter region of Sfrp4 gene in the foetal brain, accounting for its decreased expression and contributing to the activation of the Wnt‐Catenin signalling. The study of PC12 cells treated with 5‐aza further approved that decreased methylation could result in the higher Sfrp4 expression. In the offspring hippocampus, protein levels of Hif1a and mRNA expression of Sfrp4 were unchanged, whereas Wnt signal pathway was inhibited. The data demonstrated that PH activated the Wnt pathway in the foetal brain, related to the hyper‐methylation of Sfrp4 as well as Hif1a signalling. Activated Wnt signalling might play acute protective roles to the foetal brain in response to hypoxia, also would result in disadvantageous influence on the offspring in long‐term.